Identifying Obstetric Mistreatment Experiences in U.S. Birth Narratives: Application of Internationally Informed Mistreatment Typologies. Issue 3 (May 2022) - Tello, Hannah J.; Téllez, Dylan J.; Gonzales, Joseph E.
Abstract: Background: Traumatic births are those resulting in feelings of distress that persist after the birth experience. Health care providers may play a role in these experiences through various forms of mistreatment. Analyses of global birth experiences have generated several domains of mistreatment. This study applies these evidence-based domains of mistreatment as an a priori coding scheme for analysis of 96 oral narratives of U.S.-based births to describe the nature of perceived mistreatment using participants' own descriptions of experiences. Method: Ninety-six transcripts of oral birth stories from 61 participants were coded using the domains of mistreatment experiences described by the Bohren et al.'s (2015) systematic review of obstetric mistreatment. Results: N = 131 individual experiences of perceived obstetric mistreatment were identified in 41 out of 96 narratives (42.7%). The most frequent types of experiences were Poor Rapport (90 incidences) and Failure to Meet Professional Standards of Care (29). Clinical Implications: Although most women in our study did not perceive any instances of obstetric mistreatment during their childbirth, over 40% of participants noted at least one event that fit one of the typologies we used as a framework for analysis. Visibility and review of the types of perceived mistreatment experiences that occur during birth enables health system leaders to implement prevention and accountability strategies. Most instances of perceived mistreatment during birth may be prevented through intentional implementation of individualized, respectful, supportive care during labor and birth. Abstract : Women may experience a tramatic birth when they perceive they have not been respected, listened to, or treated kindly during the childbirth process. Procedures and protocols that are routine to nurses, midwives, and physicians are not always understood or desired by women giving birth. In this study, narratives of women who gave birth in the United States reveal more effort is needed to make sure all those who experience childbirth are treated with the respect they deserve.